Efektifitas Pendekatan Pembelajaran Kewirausahaan Berbasis Andragogi terhadap Motivasi dan Kreativitas Siswa Sekolah Dasar - Wiwin Nur Istiqomah; Nurul Awaliyah Mukhlis; Nasihkol Haromain; Siti Lailiyah (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2023)
This article informs the effectiveness of andradogy-based entrepreneurship learning on the motivation and creativity of unggulan Boarding School Roudhotul Ulum Pilang Sidoarjo elementary school students, East Java. The type of research in this article is a quasy experimental with a pretest-posttest control design. The research subjects were taken from class V, which consisted of 31 students divided into 2 groups, namely 16 students in the experimental group and 15 students in the control group. Analysis of the data used using descriptive analysis and parametric analysis. The results of the analysis test showed an increase in motivation and creativity scores for the experimental class. Even multivariate analysis found a relationship between learning entrepreneurship andradogy approach and motivation of 40.154 and creativity of 41.246 with a value less than 0.05. In this case, there are differences in motivation and creativity in andradogy-based entrepreneurship learning compared to conventional learning models. So, it can be concluded that learning entrepreneurship with the andradogy approach is effectively used to in increase the motivation and creativity of elementary school students. Artikel ini menginformasikan efektivitas pembelajaran kewirausahaan berbasis andradogi terhadap motivasi dan kreativitas siswa sekolah dasar Unggulan Boarding School Roudhotul Ulum Pilang Sidoarjo Jawa Timur. Jenis penelitian dalam artikel ini adalah quasy experimental dengan pretest-posttest control design. Subjek penelitian diambil dari kelas V yang berjumlah 31 siswa yang terbagi dalam 2 kelompok, yaitu 16 siswa kelompok eksperimen dan 15 siswa kelompok kontrol. Analisis data yang digunakan menggunakan analisis deskriptif dan analisis parametrik. Hasil uji analisis ada peningkatan skor motivasi dan kreativitas untuk kelas eksperimen. Bahkan analisis multivariant menemukan hubungan antara pembelajaran kewirausahaan pendekatan andradogi dan motivasi sebesar 40,154 dan kreativitas sebesar 41,246 dengan nilai kurang dari 0,05. Dalam hal ini ada perbedaan motivasi dan kreativitas pembelajaran kewirausahaan berbasis andradogi dibanding dengan model pembelajaran konvensional sehingga dapat disimpulkan, bahwa pembelajaran kewirausahaan dengan pendekatan andradogi efektif digunakan untuk meningkatkan motivasi dan kreativitas siswa sekolah dasar.